Improvement of the Technology of Liquidation of Steel Alloys in A Basic Lined Furnace - Saidkhodjaeva Shokhista; Gulyamov Saidsulton; Hkamroev Vokhid; Urinboev Umidjon; Abdullaev Rustam (Zien Journals, 2023)
In this article, in order to obtain reinforcement products from high – quality steel alloys, the chemical composition of A500C steel alloy was developed. In addition, the mode of liquefaction of steel alloy in an electric arc furnace was considered, and quality cast products were obtained by adding a modifier to the composition of the alloy during the liquefaction process.
Keywords: steel; alloy; slag; electric arc furnace